Frost-Heave Deformation and Prevention Technology of Power Transmission and Transformation Foundation under Extreme Boundary Temperature. Issue 4 (April 2021) - Wang, Shijun; Jiang, Mingjun; Xu, Bo
Abstract: Freezing and thawing disasters in seasonal frozen soil areas seriously affect the safety of power transmission and transformation projects. Studying the distribution of soil temperature and deformation under thermal insulation foundations is an important basis for the analysis of foundation stability in seasonal frozen soil areas. The thermal protection structure is closely related to the thickness of the insulation layer and the external thermal field. This dissertation takes the typical tower foundation of the 750 kV Hexi Power Grid Project and the geological conditions of the Shule River area in Gansu as the research objects. The theoretical analysis and numerical simulation methods are used to consider the impact of different thermal protection structures on the tower foundation and surrounding soil under extreme boundary temperatures. The influence of body deformation, stress, and temperature changes was analyzed. Through comparative analysis, it is found that the optimized structural form can effectively increase the temperature of the soil in extreme environments, avoid frost heave, and meet the design requirements for bearing capacity. In addition, the thermal-mechanical coupling analysis of the foundations of the initial temperature fields of different boundaries is carried out, and the applicability of the insulation foundation under different boundary conditions is discussed.